Automation of Assembly and Installation Processes in Mechanical Engineering (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Automation of assembly and installation processes in mechanical engineering is an important task that can help improve production efficiency and reduce production costs. This annotation will consider an approach to automating assembly and installation processes in mechanical engineering.